Habitat sharing and interspecies interactions in caves used by bats in the Republic of Congo - Morgane Labadie; Serge Morand; Mathieu Bourgarel; Fabien Roch Niama; Guytrich Franel Nguilili; N’Kaya Tobi; Alexandre Caron; Helene De Nys (PeerJ)
Bats play key roles in ecosystem functions and provide services to human populations. There is a need to protect bat populations and to mitigate the risks associated with pathogen spillover. Caves are key habitats for many bat species, which use them as roosting and breeding sites. Caves, bats and their guano also attract many other animals along trophic chains which might favor direct or indirect interspecies interactions. Two caves hosting colonies of insectivorous bats have been investigated in the Republic of Congo to characterize habitat sharing and interactions between bats, humans and animals. We set up a camera-trap monitoring protocol during 19 months at the entrance of and inside each cave. Our results demonstrated the richness and complexity of the species interactions around and within these caves. We identified and/or quantified mainly rodents, but also numerous categories of animals such as insects, birds, reptiles and carnivores using the caves. We investigated the temporal variation in the use of caves and the potential interactions between humans, wild animals and bat colonies. Our study contributes to the understanding of the interface and interactions, for the first time quantified, between cave-dwelling animal species, including humans. This knowledge is important to promote the conservation of cave ecosystems and better understand the ecology of infectious diseases.